Telehealth in arts therapies for neurodevelopmental and neurological disorders: a scoping review - Reitere, Ērika; Duhovska, Jana; Karkou, Vicky; Mārtinsone, Kristīne (Frontiers in Psychology, 2024)
BackgroundArts therapies, encompassing art therapy, music therapy, drama therapy, and dance movement therapy with the broader practice of expressive arts therapies, have demonstrated positive outcomes in the treatment of neurodevelopmental and neurological disorders (NNDs). Integrating arts therapies into telehealth has become increasingly important to improve accessibility for people with mobility impairments or those living in remote areas. This study aims to map the existing body of literature to provide an in-depth overview of telehealth in arts therapies for individuals with NNDs.MethodologyThis scoping review followed the PRISMA guidelines. Six databases were systematically searched, with 2,888 articles screened for eligibility. Inclusion criteria focused on primary research peer-reviewed articles in English that addressed telehealth arts therapies for NNDs.ResultsSeventeen telehealth studies published between 2009 and March 2024 were included, with a notable increase in publications after 2020. The studies covered various neurodevelopmental disorders, including autism spectrum disorders, attention deficit hyperactivity disorder (ADHD), Rett syndrome, and neurological disorders such as stroke, epilepsy, cerebral palsy, central nervous system (CNS) tumors, dementia, Alzheimer’s disease, Parkinson’s disease, spinal cord injuries, and mild cognitive impairment. Music therapy was the most widely studied modality. Interventions ranged from therapeutic singing and songwriting to virtual reality experiences. Different platforms and specialized virtual environments were used alongside pre-recorded sessions. Positive benefits included psychological enrichment, social connectivity, cognitive improvements, and brain changes, although some studies reported mixed or no significant effects in certain areas.ConclusionTelehealth in arts therapies significantly benefits individuals with NNDs, improving accessibility and providing psychological, emotional, social, and cognitive benefits. The positive benefits observed highlight the potential of these interventions to improve overall well-being and daily functioning. Future research may focus on high-quality qualitative studies and neuroimaging assessments to further validate the impact of telehealth arts therapies.